Membangun Jembatan antara Matematika dan Coding: Kajian Sistematis terhadap Kurikulum Terpadu STEM - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Rini, Puput Puspito; Slamet, Tri Setyo (Yayasan Education and Social Center, 2025)
This article presents a systematic review of the integration of mathematics and coding in the integrated STEM (Science, Technology, Engineering, and Mathematics) curriculum. The background of this research is based on the need to improve students' 21st century skills, especially in problem solving, computational thinking, and creativity. The main objective of this study is to identify basic mathematical concepts relevant to coding, the basic principles of coding in STEM contexts, as well as the role of mathematics in designing and analyzing STEM algorithms. The method used includes a systematic literature search through various databases such as JSTOR, ScienceDirect, and Google Scholar, using relevant keywords such as